Pembelajaran Madrasah Diniyah Takmiliyah dalam Meningkatkan Kemampuan Siswa Menguasai Mata Pelajaran Sekolah Formal - Kholifatun Ni’mah (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
This thesis examines the Learning of Madrasah Diniyah Takmiliyah Al Hidayah in Penganten Village, Balen District, Bojonegoro Regency in improving students' ability to master formal school subjects by carrying out learning planning activities. Even though they don't use lesson plans and syllabus, they still carry out planning. This research is a qualitative research that aims to determine the learning of Madrasah Diniyah Takmiliyah Al Hidayah in Penganten Village, Balen District, Bojonegoro Regency in improving students' ability to master formal school subjects. From the results of this study it was found that learning at Madrasah Diniyah Al Hidayah was able to improve students abilities in formal school subjects. Because after every Madin learning, all students are required to study formal school subjects. This children have special time to study formal school lessons. It turns out that eith this learning, students abilities in formal subjects can increase. All of that can be proven by student learning out comes in report cards. Based on the recap of student learning out comes at MI 2 Bride and Groom in grade 5, ranks 1 – 3 are occupied by students who take part part in learning at Madin Al Hidayah, as well as students from SDN III Bride. Those who take lessons at Madin Al Hidayah also have satisfactory achievements. For grade 4 SDN III Bride and Groom ranks 1 and 2 are also occupied by students who take part in learning at Madin Al Hidayah.